ANALISIS STRATEGI PELAYANAN UNTUK MENINGKATKAN JUMLAH PELANGGAN PADA PT. JAYA MASAWAN PALEMBANG SQUARE - Muhammad Iqbal (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2021)
ABSTRACTThis final report review of the strategy in the Ministry increased the number of customers. This research aims to answer the question of who is to be questioned in the study, that is, knowing how the history of the establishment of PT Jaya Masawan Palembang Square, the extent to which the service strategies already applied, and how the PT Jaya Masawan Palembang Square strained relations with its employees. The writing of the final report is presented in a descriptive qualitative in order to obtain an overview of a variety of information related to servicing strategy for increasing the number of customers. Method of data collection using the study documents, interviews, observation and study of the literature. The data obtained were analyzed qualitatively and then presented in a descriptive. The results showed that PT Jaya Masawan Palembang Square always give good service quality, the Chairman of PT Jaya Masawan Palembang Square trying to recruit people who are experts in the field of sales support, friendly employees and providing incentives, as well as the attempt to provide individually high attention to its customers. In addition, good cooperation with the employees will also affect the level of quality customer service.Key words: strategy of the Ministry, the number of customers.